2018
DOI: 10.1073/pnas.1717838115
|View full text |Cite
|
Sign up to set email alerts
|

Global peatland initiation driven by regionally asynchronous warming

Abstract: Widespread establishment of peatlands since the Last Glacial Maximum represents the activation of a globally important carbon sink, but the drivers of peat initiation are unclear. The role of climate in peat initiation is particularly poorly understood. We used a general circulation model to simulate local changes in climate during the initiation of 1,097 peatlands around the world. We find that peat initiation in deglaciated landscapes in both hemispheres was driven primarily by warming growing seasons, likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 38 publications
5
101
1
Order By: Relevance
“…The effect of climate change on peatland initiation and expansion is not well understood and currently a topic of active research (Morris et al, 2018). We found that peatland expansion is almost linear since the beginning of the Holocene (Figure 7a), leading to a total area of 3.1 million km 2 occupied by peatlands across the pan‐Arctic in by the year 2000 (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of climate change on peatland initiation and expansion is not well understood and currently a topic of active research (Morris et al, 2018). We found that peatland expansion is almost linear since the beginning of the Holocene (Figure 7a), leading to a total area of 3.1 million km 2 occupied by peatlands across the pan‐Arctic in by the year 2000 (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although taken individually their size is negligible compared to vast high latitude or tropical peatlands, they store between ~1,200 (Cooper et al, ) and ~1,500 Mg C ha −1 (Hribljan et al, ), which concurs with the average storage of 1,330 Mg C ha −1 defined for boreal peatlands (Gorham, ). Summed together mountainous peatlands may represent a valuable carbon stock that needs to be defined globally, understood (Morris et al, ) and preserved through current global changes. Because of their remote location, peatlands in mountains are much less studied than their lowland counterparts and only a few studies have investigated their carbon dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Permafrost soils in general could become carbon sources with warming through greater aerobic (CO 2 ) and anaerobic (CH 4 ) decomposition rates (Natali et al, ; Schuur et al, ). However, longer, warmer growing seasons and changes in Arctic precipitation regimes (Bintanja & Selten, ; Kattsov et al, ; Kopec et al, ) may stimulate carbon capture through enhanced plant productivity in peatlands and the transition of minerotrophic wetlands into organic peatlands (Charman et al, , ; Gallego‐Sala et al, ; Morris et al, ). Recent evidence shows an inconsistent response of Arctic and sub‐Arctic peatlands to warming in terms of carbon accumulation (Zhang, Gallego‐Sala, et al, ).…”
Section: Introductionmentioning
confidence: 99%